2023
DOI: 10.1108/jcefts-05-2023-0019
|View full text |Cite
|
Sign up to set email alerts
|

The interplay of entrepreneurial motivations, job attractiveness and family-owned SMEs growth: evidence from China Pakistan Economic Corridor region

Irfan Saleem,
Muhammad Ashfaq

Abstract: Purpose The purpose of this study is to provide a nuanced explanation of the linkage between entrepreneurial motivations, job attractiveness and growth of family-owned small and mid-sized enterprises (SMEs) using expectancy and institutional theories. Design/methodology/approach The data was collected from small family business owners and job seekers in the same companies during interview time using a simple random technique. Findings The study found that three EMs among small business owners play a pivota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…Technological innovation. Following Wu et al (2023) [ 36 ], the logarithm of the number of patents per 10,000 people was used to measure technological innovation.…”
Section: Methodsmentioning
confidence: 99%
“…Technological innovation. Following Wu et al (2023) [ 36 ], the logarithm of the number of patents per 10,000 people was used to measure technological innovation.…”
Section: Methodsmentioning
confidence: 99%
“…Entrepreneurship plays a pivotal role at the individual, corporate, and institutional levels, fostering economic development and progress, making it a vital catalyst for the sustained vitality of the contemporary economy [51][52][53]. In that context, this study used time series data collected from the World Bank database to investigate the relationship between unemployment and entrepreneurship in Namibia.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, the results also align with the emphasis of Aku-sika [38] that entrepreneurship drives economic growth by addressing social challenges. Thus, it is essential for the government to reform policies for emerging businesses through the implementation of tailored measures that optimize the business climate for domestic entrepreneurs [51]. Aside from that, Feki and Mnif [19] reveal the presence of both the refugee effect and the Schumpeter effect in Tunisia, where an increase in unemployment results in self-employment and an increase in self-employment reduces unemployment.…”
Section: Empirical Literature Reviewmentioning
confidence: 99%
“…According to data from the U.S. Bureau of Labor Statistics (2020), approximately 50% of new companies cease operations within five years of establishment. These failed entrepreneurial attempts may have significant negative impacts on entrepreneurs, including financial loss, career interruption, and psychological stress.Some scholars have also applied the Expectancy Theory and Institutional Theory to research and found that in underdeveloped trade regions like the China-Pakistan Economic Corridor, three entrepreneurial motives among small business owners play a crucial role in the growth of family-owned small businesses [1] . Despite the undeniable negative effects of failure, people often say that "failure is the mother of success."…”
Section: Introductionmentioning
confidence: 99%